Fading Evaluation in the 60 GHz Band in Line-of-Sight Conditions. (7th August 2014) - Reig, J.; Martínez-Inglés, M.-T.; Rubio, L.; Rodrigo-Peñarrocha, V.-M.; Molina-García-Pardo, J.-M.
Abstract : An exhaustive analysis of the small-scale fading amplitude in the 60 GHz band is addressed for line-of-sight conditions (LOS). From a measurement campaign carried out in a laboratory, we have estimated the distribution of the small-scale fading amplitude over a bandwidth of 9 GHz. From the measured data, we have estimated the parameters of the Rayleigh, Rice, Nakagami- m, Weibull, andα -μ distributions for the small-scale amplitudes. The test of Kolmogorov-Smirnov (K-S) for each frequency bin is used to evaluate the performance of such statistical distributions. Moreover, the distributions of the main estimated parameters for such distributions are calculated and approximated for lognormal statistics in some cases. The matching of the above distributions to the experimental distribution has also been analyzed for the lower tail of the cumulative distribution function (CDF). These parameters offer information about the narrowband channel behavior that is useful for a better knowledge of the propagation characteristics at 60 GHz.